THE USE OF COMIC STRIPS AS AN ENGLISH TEACHING MEDIA FOR JUNIOR HIGH SCHOOL STUDENTS - Rokhayani, Atik; Perwikasih Utari, Aisyah Ririn (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
Nowadays, teachers have to be creative in delivering materials to the students. Ideally, teaching media are needed to support the success of teaching and learning processes. In English classes, teachers have to create a good atmosphere using interactive teaching media. The objectives of this paper are (1) to know whether Printed Material in the form of Comic Strips can improve the English vocabulary of the students of SMP 2 Bae Kudus, (2) to describe the strength and the weaknesses of comic as a means of teaching English. This is action research was conducted at Class VIIA of SMP 2 Bae Kudus consisting of 30 learners. Before conducting the research, the writers administered a pr- test to know the studentsâ mastery of vocabulary. The result of the pre-test shows that the mean score was 68.27, while the standard score (KKM) is 75. Then, the writers in collaboration with the English teacher did Cycle I using Comic Strips. The mean score of a test proceeding Cycle I was 76.97. So, the writers continued to do Cycle II. In Cycle II, the writers also gave evaluation to the students. The mean score of the test proceeding Cycle II was 85.10. In delivering the materials, the teacher felt it easier to deliver teaching materials using comic strips.